Analsisis Penerapan Media Pembelajaran dalam Proses Belajar Mengajar pada Jenjang Sekolah Dasar - Lumbantobing, Winda Lidia; Sumarni, Margaretha Lidya; Saputro, Totok Victor Didik (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Learning media in elementary schools is increasingly needed to facilitate the teaching and learning process. There is an urgency for learning media in elementary schools in the current digital era. First, increase the attractiveness of learning. Interactive and interesting learning media can provide a pleasant learning experience for students so that it can increase motivation and interest in learning. Second, increase the effectiveness of learning. Learning media can help students understand concepts more easily and quickly. Third, increase student participation. This can increase student involvement and participation in learning. Fourth, increase student creativity. Learning media with features such as image and video content can stimulate imagination and open up students' possibilities for creativity and innovation. Fourth, facilitate distance learning. Currently, in the COVID-19 pandemic situation, the use of learning media is very important to support distance learning in elementary schools. Therefore, the use of learning media in elementary schools in the current digital era needs to be implemented well and integrated into the curriculum, so that it can provide maximum benefits for students in the learning process. For this reason, this research focuses on analyzing the application of learning media in the learning and teaching process at the elementary school level. The aim of this research is to find out a clear picture of how learning media is implemented at the elementary school level, specifically in the West Kalimantan-Malaysia border area. The stages of the research method used are in the first stage, preparing data collection tools. The second stage in the research carried out was data collection and collection. The initial activity was observation by inspecting elementary schools in Bengkayang Regency. A literature review is carried out to look for data or source support that is relevant to the research. Interviews and Focus Group Discussions (FGD) will be conducted online and offline. The questionnaire that has been prepared will be shared online using Google Forms. The third or final stage is the stage of data preparation and recapitulation.Keywords: instructional media, elementary school